Increased C‐reactive protein concentration and suicidal behavior in people with psychiatric disorders: A systematic review and meta‐analysis. (25th August 2021) - Miola, Alessandro; Dal Porto, Veronica; Tadmor, Tal; Croatto, Giovanni; Scocco, Paolo; Manchia, Mirko; Carvalho, Andre F.; Maes, Michael; Vieta, Eduard; Sambataro, Fabio; Solmi, Marco
Abstract: Objective: Suicide is a leading cause of death worldwide. Identifying factors associated with suicidality (suicidal ideation [SI]/suicidal behavior) could increase our understanding of the pathophysiological underpinnings of suicide and improve its prevention. Methods: We conducted a systematic review (PubMed/PsycInfo/Cochrane databases, up to September 2020) and random‐effect meta‐analysis including observational studies comparing peripheral C‐reactive protein (CRP) levels in suicidal versus non‐suicidal patients affected by any psychiatric disorder and healthy controls (HC). Primary outcome was the CRP standardized mean difference (SMD) between patients with high suicidality versus those with absent or low suicidality. Secondary outcomes were SMD of CRP levels between those with suicide attempt versus no suicide attempt, as well as between those with (high) versus low or absent SI. Quality of included studies was measured with Newcastle‐Ottawa scale. Results: Out of initial 550 references, 21 observational studies involving 7682 subjects (7445 with mood disorders or first‐episode psychosis, 237 HC) were included. A significant association of CRP levels with suicidality (SMD 0.688, 95% CI 0.476–0.9, p  < 0.001) emerged. CRP levels were higher in individuals with high SI (SMD 1.145, 95% CI 0.273–2.018, p  = 0.010) and in those with suicide attempt (SMD 0.549, 95%CI 0.363–0.735, p  < 0.001) than non‐suicidal individuals (either patients or HC). Main analyses were confirmed in sensitivity analysis (removing HC), and after adjusting for publication bias. The cross‐sectional design of included studies, and the high heterogeneity of diagnosis and treatment limit the generalizability of these results. Median quality of included studies was high. Conclusion: CRP is associated with higher suicidality in patients with mental disorders. Large cohort studies longitudinally monitoring CRP levels are needed to explore its longitudinal association with suicidality.